Patologi Birokrasi dalam Pelayanan Administrasi Kependudukan di Dinas Kependudukan Dan Pencatatan Sipil Kota Baubau - Syawaluddin, Syawaluddin; Abidin, Zainul; Islamy, La Ode Syaiful (Universitas Medan Area, 2024)
This article explores bureaucratic pathology in the administration of population services at the Department of Population and Civil Registration in Baubau City, focusing on the forms, causes, and solutions to these issues. Utilizing theories from Siagian and Dwiyanto, data were collected through interviews, observations, and document studies, and then analyzed qualitatively. During the analysis, irrelevant data were discarded, and related categories were integrated into a cohesive theme for interpretation. The study's findings reveal that the primary form of bureaucratic pathology is the lack of knowledge and skills among staff, leading to inaccuracy, low work quality, and incorrect actions. The second form of pathology involves bribery and gratuities, while the final issue is staff laziness. The causes of these pathologies are linked to public apathy towards regulations and certain staff members exploiting the situation by soliciting bribes. Proposed solutions include individual approaches, such as placing staff according to their expertise and enhancing discipline, and organizational approaches through the use of information technology, outreach programs, and technical training. These implementations aim to improve service quality and reduce unhealthy bureaucratic practices in Baubau City.